The complexities of Triana collections: Unraveling the original materials of Pterogastra major (Melastomataceae) - Nunes Da Silva, Diego; Reinales, Sandra; Fernandes Guimarães, Paulo José (Phytotaxa, 2024)
The monophyletic tribe Melastomateae Bartling (1830: 329) comprises 44 genera distributed across America, Africa and Asia (Veranso-Libalah et al. 2022). Among the Neotropical genera, Pterogastra Naudin (1850: 32) + Pterolepis (DC.) Miquel (1840: 72) form an intriguing clade that is sometimes considered sister to the Neotropical clade of Melastomateae, sister to the Paleotropical clade, or sister to both clades (see a detailed history in Veranso-Libalah et al. 2022; see also Penneys et al. 2022). The genus Pterogastra occurs in Brazil, Bolivia, Peru, Ecuador, Colombia, Venezuela and Guyana (Renner 1993; Silva et al. 2023), and is composed by three herbaceous, subshrubby and shrubby taxa: P. divaricata (Bonpl.) Naudin (1850: 33), P. divaricata var. glabra (Gleason) Renner (1994: 68), and P. minor Naudin (1850: 33) (Renner 1994). Pterogastra major Triana (1872: 40), a heterotypic synonym of P. divaricata (Renner 1994), was described based on at least four collections: Bonpland s.n. collected next to Villavicencio (Colombia), Goudot s.n. collected in Chaparral (Colombia), Triana s.n. probably collected in Fusagasugá and Susumuco (Colombia), and Mathews 1278 collected next to Moyabamba (Peru). In the taxonomic revision of the genus, the specimen Triana s.n. deposited at BM was selected as the lectotype of Pterogastra major (Renner 1994). Nevertheless, after investigating the Triana collections associated with the original material of P. major and based on the information contained in each label, we reassessed the nomenclatural status of each exsiccate, providing clarifications for all materials of this species collected by Triana.